Variability of External Genetic Characteristic of Kokok Balenggek Chicken in West Sumatera, Indonesia - Arlina , Firda; Abbas, Hafl; Anwar, Sarbaini; Jamsari (International Journal of Poultry Science, 2014)
Kokok Balenggek chicken is one of the rare indigenous chickens in Indonesia. They are unique as they produce a melodious song like crow. They have syllabic diversity, as each portion of the call can be composed with different pitches and vocalizations. The identification and characterizations of local adorn chicken is very important for animal conservation. A research was conducted in west Sumatera to identify the genetic variability of the external genetic characteristic of Kokok Balenggek chicken. This research was conducted in a limited area of Solok district West Sumatera, Indonesia. About 203 (111 males and 92 females) Kokok Balenggek chicken were observed. The varieties are based on base colour of feather, colour of the plumage, flick feather, pattern of feather, shank colour and comb types. The method were used to analyze the rate of purity and native gene, the frequency of autosomal and sex-linked of the genes, feather pattern, rate of introgression from the exotic breed of Rhode Island Red, White Leghorn and of Barred Plymouth Rock. The research showed that the highest controlling genes characteristic external of kokok Balenggek chicken are coloured (ii), wild type pattern (e+), plain feather (ss) golden flick feather (ss), yellow shank coloured (Id_) and single comb (pp). A constitution on external genetic characteristic of Kokok Balenggek is ii e+_bbssId_pp. while The purity gene of Kokok Balenggek chicken has only 45.30%. Its genetic introgression is affected by the exotic breed from Europa and America with genetic introgression value of 0.5470. According to the rate of heterozygosity value of kokok Balenggek chicken varied within 29.41%. In conclusion, the Kokok Balenggek chickens show heterogeneity in the external genetic. To complete a set of their characterization further studies are needed on their quantitative traits and the molecular composition.